Effects of Acitretin Treatment on Hearing in Patients with Psoriasis Vulgaris - Başak Mutlu; Merve Torun Topçu; Ayşe Serap Karadağ; Yasemin Gündüz; Mahmut Tayyar Kalcıoğlu (The Turkish Journal of Ear Nose and Throat)
Objective: In this study, we aimed to compare the hearing thresholds and outer hair cell functions of patients with psoriasis vulgaris (PV) with healthy individuals and to investigate the ototoxic effects of acitretin treatment (AT) in patients with PV. Materials and Methods: This study included 23 patients with PV who required treatment with acitretin as well as 23 healthy individuals. Conventional and extended high-frequency pure-tone audiometry and transient-evoked otoacoustic emission tests were performed at regular intervals during the 24 weeks of acitretin treatment. Results: During the acitretin treatment for the PV group, the hearing thresholds of 4,000 Hz (right ear, p=0.004) presented a significant difference that did not have a worsening effect. The signal-to-noise ratios of TEOAE did not show a significant difference. At 24 weeks of AT, the changes in the hearing thresholds (4,000 Hz) and TEOAE signal-to-noise ratios did not indicate any worsening owing to acitretin. According to the ASHA criteria, there was no significant evidence of ototoxicity related to acitretin. According to the TUNE ototoxicity grading system, it was seen that at 24 weeks of AT, all the patients with psoriasis were scored as grade 0 (no hearing loss). Conclusion: This study showed that acitretin does not have an ototoxic effect when it is used to treat PV in the recommended treatment doses.